Awareness Regarding Hiv/Aids Among College Students In Khyber Pakhtunkhwa (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: HIV is still a major global health problem. In 2009, globally there were an estimated 2.6 million (2.3 million–2.8 million) incident cases of HIV. According to UNAIDS in 2009 a total of 98,000 (79,000 – 120,000) people are living with HIV in Pakistan. Pakistan was classifi ed as a low-prevalence country with many risk factors that could lead to the rapid development of an epidemic. In 2004, a concentrated outbreak of HIV was found among Injecting Drug Users (IDUs) in Karachi, where over 20 percent of those tested were found to be infected. Prevention efforts are beginning to bear fruit, with indications of behaviour change and declines in prevalence rates in a number of high-burden countries. The study aimed to determine the level of awareness among college students regarding HIV/AIDS in Khyber Pakhtunkhwa. Methodology: This cross sectional study was conducted in the two colleges of Peshawar. A total of sixty students were enrolled in the study thirty from each college through random sampling. The students were from second year class. One of the colleges was from Public Sector, Government College Peshawar and the other was from private sector Peshawar Model College (PMC). Results: It was interesting to note that 60% of the students of Government (Govt.) college and 70% of the students of PMC knew that a person having a healthy look might have been infected with HIV. Seventy percent of the students of Govt. college and 60% of the students of PMC reported that there is no curative treatment for HIV/AIDS. Major source of information regarding HIV/AIDS was through TV and friends. Condoms were regarded as main protection from HIV/AIDS as 35% of the students of Govt. College and 40% of the students of PMC reported as a method of prevention, Other preventive methods were also reported by the students. Conclusion: The study depicted that there remain gaps in certain areas of awareness of the students which needs initiation of HIV/AIDS awareness programmes among college students. DOI: http://dx.doi.org/10.3126/saarctb.v8i2.5900 SAARCTB 2011; 8(2): 37-41